Tindak Tutur Direktif dalam Podcast Bertema Mindset di Kanal YouTube Suara Berkelas - Naya Deansita Maheswari; Shofa Saida Khusna; Haufa Dilla; Indah Berlianne Sulistyawati; Elsa Dwi Auliya; Asep Purwo Yudi Utomo; Ngabiyanto Ngabiyanto (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Podcasts have become one of the fastest-growing forms of digital media in the modern communication era due to their persuasive and easily accessible nature. The Mindset podcast on the YouTube channel SUARA BERKELAS presents various motivational utterances that are interesting to analyze from a pragmatic perspective, particularly in the form of directive speech acts. This study aims to describe the types of directive speech acts found in the Mindset podcast, analyze the linguistic strategies employed by the speakers, and examine their communicative implications for the audience. The research employed a qualitative approach with pragmatic analysis through stages of transcription, classification, and contextual interpretation. Data were obtained from selected episodes using purposive sampling and analyzed using Austin’s (1975) and Searle’s (1969) speech act theories. The findings revealed nine types of directive speech acts commands, invitations, suggestions, appeals, prohibitions, persuasion, urgings, requests, and instructions with commands and invitations as the most dominant. These results indicate that the podcast serves as a motivational medium that not only conveys information but also encourages listener participation through persuasive linguistic strategies. This research contributes to the development of pragmatic studies in digital media and provides insights for content creators and communication practitioners in designing more engaging and inspiring messages.